Are two strategies better than one? Manipulation of seed density and soil community in an experimental prairie restoration. Issue 5 (20th May 2019) - Lubin, Terra K.; Schultz, Peggy; Bever, James D.; Alexander, Helen M.
Abstract : Restoration practitioners have a variety of practices to choose from when designing a restoration, and different strategies may address different goals. Knowledge of how to best use multiple strategies could improve restoration outcomes. Here, we examine two commonly suggested strategies in a single tallgrass prairie restoration experiment: increased forb sowing density and prairie soil inoculation. We designed a study with two different forb seeding densities. Within these densities, we transplanted seedlings into 1‐m 2 plots that had been grown in either a whole prairie soil inoculum or sterilized prairie soil. After 4 years, we found positive effects of both high forb sowing density and inoculation treatments on the ratio of seeded to nonseeded plant cover in these plots, and negative effects of both treatments on nonseeded plant diversity. No effects of either treatment were seen on seeded plant diversity. Each strategy also affected the plant community in different ways: high forb sowing density increased seeded forb richness and decreased native nonseeded plant cover, while inoculation decreased non‐native cover, and tended to increase average successional stage of the community. These effects on restoration outcome were typically independent of each other, with the result that plots with both manipulations had the most positive effects on restoration outcomes. We thus advocate the combined use of these restoration strategies, and further studies which focus on both seeding and soil community manipulation in restoration.